Practice and Reflection on Joint Operation Scheme of Water Projects of Pearl River Basin:Flood Control in 2022 - HUANG Feng; HOU Guibing; LI Yuanyuan (Renmin Zhujiang)
The joint operation scheme of water projects compiled year by year in the Pearl River Basin comprehensively considers the current situation of flood control in the basin and the practical experience of dispatching and continuously expands the water projects included in the scope of joint operation,which optimizes and adjusts the existing dispatching modes of water projects.It has now become an important non-engineering measure for real-time flood control operation.In June 2022,the Pearl River Basin experienced a catastrophic flood,second only to the one in 1915.Under the guidance of the basin joint operation scheme of water projects,and based on the flood characteristics and flood control situation,the Longtan Reservoir plays a core role,jointly operated with various types of water projects such as the reservoirs in the main and tributary rivers,flood storage and detention areas,and floodgates.It coordinates the overall situation of the river basin and fully taps into the flood control and storage potentials of water projects,successfully dealing with the 2022 flood.This paper sorts out the application of the joint operation scheme of water projects during the flood period in 2022 and analyzes the application mode and dispatching effects of the joint operation of water projects under different water inflow situations.Then,the deficiencies of the flood control joint operation scheme of water projects exposed during the flood period are summarized.Discussions are made on the optimization space of flood control operation mode of water projects with the Longtan as the core.Finally,the countermeasures and suggestions for the further improvement of the joint operation scheme of the Pearl River Water Project are proposed.